SEASONAL EFFECT ON MILKABILITY OF KANKREJ COWS (Indian Journal of Animal Production and Management, 2014)
An experiment was conducted on 20 lactating Kankrej cows divided in four groups according to lactation number one to four and initial stage of lactation with almost same production. Highly significant (P
Keywords: Milkability; Lactation; Kankrej